James Mabbe (ed. de José María Pérez Fernández). The Spanish Bawd - Rachel Scott (Universitat de Girona; Universitat Autònoma de Barcelona, 2016)
James Mabbe (ed. de José María Pérez Fernández) The Spanish Bawd, MHRA Tudor and Stuart Translations, vol. 10 London, Modern Humanities Research Association, 2013, 412 p. ISBN 978-1-78188-148-4